Improving Students’ Reading Comprehension through RCRR (Read, Cover, Remember, Retell) Strategy at the Eight Grade of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan in 2022/2023 - Florencia Zebua; Afore Tahir Harefa; Elwin Piarawan Zebua; Hasrat Sozanolo Harefa (Universitas Muhammadiyah Enrekang, 2023)
Reading comprehension is the process of the reader's mind in constructing meaning of what has been read. In the reality, the students Strategy at the Eighth Grade of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan have reading comprehension problems. There are also problems faced by students: Students do not understand the meaning of the words in the text, Students cannot find the main ideas in the text, Students forget the text they have read. Based on these problems, this study aims to overcome the problems faced by students and improve students' abilities in reading comprehension by using the RCRR Strategy (Read, Cover, Remember, Retell) in class VIII-B students of SMP Negeri 2 Dharma Caraka in 2022/2023. This research uses Classroom Action Research (CAR) which consists of Planning, Action, Observation, and Reflection. This research was conducted in two cycles consisting of two meetings in each cycle. The results of the research in cycle I showed that there were 18 students who did not complete the MCC out of 32 students and the average student score was 63.12. The lowest score is 40 and the highest is 80. In cycle II all students pass MCC with an average student score of 91.25 with the lowest score 70 and the highest score 100. Based on the research results, the researchers concluded that RCRR (Read, Cover, Remember, Retell) improved students' vocabulary and overcome the students' problem in this research.